2018
DOI: 10.1098/rstb.2017.0392
|View full text |Cite
|
Sign up to set email alerts
|

Fungarium specimens: a largely untapped source in global change biology and beyond

Abstract: One contribution of 16 to a theme issue 'Biological collections for understanding biodiversity in the Anthropocene'.For several hundred years, millions of fungal sporocarps have been collected and deposited in worldwide collections (fungaria) to support fungal taxonomy. Owing to large-scale digitization programs, metadata associated with the records are now becoming publicly available, including information on taxonomy, sampling location, collection date and habitat/substrate information. This metadata, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 79 publications
0
44
0
1
Order By: Relevance
“…Over large scales, abiotic factors including temperature (Zhou et al, ) and pH (Glassman, Wang, & Bruns, ; Tedersoo et al, ) have been shown to be the strongest predictors for fungal distributions (Timling, Walker, Nusbaum, Lennon, & Taylor, ). The importance of temperature in determining biogeographical patterns among fungi (Andrew, Diez, James, & Kauserud, ) highlights the potential sensitivity of these communities to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Over large scales, abiotic factors including temperature (Zhou et al, ) and pH (Glassman, Wang, & Bruns, ; Tedersoo et al, ) have been shown to be the strongest predictors for fungal distributions (Timling, Walker, Nusbaum, Lennon, & Taylor, ). The importance of temperature in determining biogeographical patterns among fungi (Andrew, Diez, James, & Kauserud, ) highlights the potential sensitivity of these communities to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Equally as important, this information can be used to target the acquisition of new material for preservation in herbarium collections. The usefulness of herbarium specimens from many years ago for DNA isolation and analysis (e.g., Malmstrom et al., ; Andrew et al., ; Heberling and Burke, ) means that locating extant populations also makes it possible to compare past and current genetic structure. Heberling and Isaac () suggested using iNaturalist as a direct supplement to new herbarium specimens by linking the online observations to the herbarium sample.…”
Section: Further Utility Of Online Natural History Platformsmentioning
confidence: 99%
“…Multiple studies have utilized museum collections to investigate wild plant–pathogen systems (Ristaino et al., ; Li et al., ; Alexander et al., ; Saville et al., ; Andrew et al., ), among other plant ecological interactions (e.g., plant–animal interaction, Beauvais et al., , or phytosociology, Hanan‐A et al., ). There are two types of natural history collections relevant to such disease‐related studies: pathogen‐centered collections that directly target and preserve the disease‐causing organism and broader plant‐centered collections that nonetheless may retain evidence of the disease occurrence and cause.…”
mentioning
confidence: 99%
“…Collections are an important resource for biodiversity research, as they provide curated specimens spanning time and space ( Funk, 2018 ; Pearce et al, 2020 ). Beyond prospecting for novel fungal diversity in dedicated mycological collections such as fungaria and culture collections ( Dentinger et al, 2016 ; Andrew et al, 2018 , 2019 ; Huang et al, 2018 ), we now recognise the potential for plant collections to be a source of fungal diversity too. Daru et al (2018) showed that sequencing dried herbarium specimens can reveal novel endophyte diversity, with the caveat that it is extremely rare to recover viable endophytes in culture.…”
Section: Introductionmentioning
confidence: 99%